1989
DOI: 10.1203/00006450-198908000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Furosemide on Body Water Compartments in Infants with Bronchopulmonary Dysplasia

Abstract: ABSTRACT. We studied the effects of a single dose ofStudies in adults with pulmonary edema (5-7) have shown intravenous furosemide on the body water compartments variable effects of furosemide on plasma volume. Davidor et al.of nine infants with bronchopulmonary dysplasia. We (5) measured plasma vol in patients with refractory edema 2 h measured total body water, extracellular water, and plasma after an intravenous dose of furosemide. These patients had a volume using deuterium oxide, sodium bromide, and Evans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…& p . 1 : Loop diuretics may acutely induce hemodynamic alterations independent of diuresis [30][31][32][33][34][35]. Reduction of interstitial edema with preservation of plasma volume was observed after administration of furosemide to adults with pulmonary edema and infants with chronic lung disease [30,[32][33][34].…”
Section: Nonrenal Effectsmentioning
confidence: 96%
See 2 more Smart Citations
“…& p . 1 : Loop diuretics may acutely induce hemodynamic alterations independent of diuresis [30][31][32][33][34][35]. Reduction of interstitial edema with preservation of plasma volume was observed after administration of furosemide to adults with pulmonary edema and infants with chronic lung disease [30,[32][33][34].…”
Section: Nonrenal Effectsmentioning
confidence: 96%
“…& p . 1 : Furosemide therapy has been used in an attempt to improve lung compliance in infants with respiratory distress syndrome (RDS) or BPD [32,34,[37][38][39][40][41]. Interestingly, the beneficial pulmonary effects of furosemide usually occurred before appreciable diuresis, indicating that local versus renal mechanisms were involved [32,34,37,40,41].…”
Section: Nonrenal Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…Usually the signs ofvenous congestion are suppressed by giving diuretics to decrease the (suspected) excess interstitial fluid. Other studies have demonstrated that administration of diuretics does not decrease plasma volume (44,45). If this also applies to individuals with left-to-right shunts, it would imply that the increase in blood volume is not disturbed by diuretic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the indicator was administered intravenously and blood samples were taken for the concentration measurements. In more recent studies, D20 or H2,sO was given orally or intragastrically and the tracer concentration in urine [4][5][6][7][8], saliva [5,9], or expired air [ 10,11 ] was used to calculate TBW.…”
Section: Introductionmentioning
confidence: 99%